Examination of the effect of differential molecular diffusion in DNS of turbulent non-premixed flames. (20th April 2017) - Han, Chao; Lignell, David O.; Hawkes, Evatt R.; Chen, Jacqueline H.; Wang, Haifeng
Abstract: The effect of differential molecular diffusion (DMD) in turbulent non-premixed flames is studied by examining two previously reported DNS of temporally evolving planar jet flames, one with CO/H2 as the fuel and the other with C2 H4 as the fuel. The effect of DMD in the CO/H2 DNS flames in which H2 is part of fuel is found to behave similar to laminar flamelet, while in the C2 H4 DNS flames in which H2 is not present in the fuel it is similar to laminar flamelet in early stages but becomes different from laminar flamelet later. The scaling of the effect of DMD with respect to the Reynolds number Re is investigated in the CO/H2 DNS flames, and an evident power law scaling (∼ Re − a with a a positive constant) is observed. The scaling of the effect of DMD with respect to the Damköhler number Da is explored in both laminar counter-flow jet C2 H4 diffusion flames and the C2 H4 DNS flames. A power law scaling (∼ Da a with a a positive constant) is clearly demonstrated for C2 H4 nonpremixed flames. Highlights: Differential molecular diffusion (DMD) in two DNS flames are examined. DMD in CO/H2 DNS flames is found to be similar to laminar flamelet. DMD in C2 H4 DNS flames is found to be different from laminar flamelet. A power law scaling of DMD against Re is observed in the CO/H2 DNS flames. A power law scaling of DMD against Da is observed in the C2 H4 flames.